MANAJEMEN AKSESIBILITAS SARANA DAN PRASARANA BAGI PENYANDANG DISABILITAS DI MASJID KOTA SELONG LOMBOK TIMUR - Asa nur Safitri (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2024)
Lombok is known by title as “Island of 1001 mosques”. Its existence on theone hand has given abetter Islamic nuance. People with disabilities are those who have physical , intellectual or acombination of both limtations. On the other hand, the number of people with disabilities in EastLombok continues to increase every year. Selong is known to the public as the capital of EastLombok district, as the capital,it is only right. Selong is improving itself to improve facilities,infrastructure and buildings for the general public. Including people with disabilities.Considering that Lombok is a paradise for mosques and considering the large number of peoplewith disabilities, mosques in the city of Selong are slowly starting to build mosque facilities thatare friendly to the disabled. Hopefully in the future, the Selong City mosque will further imroveits facilities, especially for the disabled so that allworshipers can worship with facilities andservices that are worth it.